Islamic-Hindu Conversion Marriages in Lingsar and Narmada Districts, West Lombok Regency from the Perspective of Islamic-Hindu Law and Social Change - Saefuddin Zohri; Lalu Muhammad Nurul Wathani; Zulkarnain (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Lombok is an island in eastern Indonesia known for its rich culture and religious diversity. Historically, Lombok has been influenced by various cultural and religious influences, initially being part of the Karangasem kingdom in Bali, with a predominantly Hindu population. However, with the spread of Islam in the region, cultural and religious acculturation has resulted in a unique blend within the community, particularly evident in conversion marriages between Muslims and Hindus in the Lingsar and Narmada districts of West Lombok. This study uses a qualitative approach to gather detailed information on the dynamics of conversion marriages in the Lingsar and Narmada districts. Data were collected through interviews with several informants, social observations, and relevant literature. This study aims to provide a comprehensive understanding of the social, legal, and cultural aspects of these marriages from the perspectives of Islamic and Hindu law and social change. This study highlights the complexity of changes in interfaith marriages, which are influenced by factors such as love, tolerance, family influence, and cultural considerations. This study examines the perspectives of Islamic and Hindu law on these marriages and the social changes in the community, which reflect different views and practices. Islamic law allows conversion marriages to Islam under certain conditions, while Hindu law allows conversion marriages to Hinduism and strictly prohibits marriages with non-Hindus, emphasizing the importance of upholding dharma. This study also investigates societal responses, identifying positive and negative perceptions that shape the acceptance or rejection of such marriages, reflecting broader social changes in society.